ISOSTATIC CONDITIONS IN SOUTHERN AND EASTERN YEMEN AND THEIR IMPORTANT GEOLOGIC IMPLICATIONS - Al-Rawi, Fitian (Iraqi Journal of Science, 2024)
Fifty-nine gravity basic stations distributed in southern and eastern Yemen are considered to obtain the regional Bouguer anomaly and isostatic maps of the covered region. The obtained maps show many high amplitude negative anomalies which are related to high elevation area and mass deficiency beneath the continental crust.Isostatically the study region seems to be overcompensated in high land, while it is nearly complete compensation in low land area. The region requires an upwelling of the mantle material to compensate the mass deficiency in the region. Such process also requires uplift in the earth’s surface, which should have a relation with the tectonic and geomorphologic processes acting in the region such erosion. A complete gravity measurement stations to cover the whole territory of Yemen will provide insight picture about the regional geology of Yemen.